Differences in HPV infection and HPV-related lesions between the cervix and anus in hiv-positive women - Cardoso Marques, Marcos Paulo; Chaves Pinto, Amanda; Soares, Leila Cristina; Brito Macedo, Jacyara Maria; Fontenelle dos Santos, Debora; Pinho Oliveira, Marco Aurelio (Revista de Ciências Médicas e Biológicas, 2021)
Introduction: the prevalence of cervical and anal human papillomavirus (HPV) infection in women infected with human immunodeficiency virus (HIV) is high. However, little is known about the differences in the susceptibility of these infections and related lesions. The aim of this study was to describe the association between the prevalence of cervical and anal HPV infection and HPV-related lesions in HIV-positive women. Methods: this study included 88 HIV-positive women attending an outpatient clinic in a university hospital. Ectocervical, endocervical, and anal samples were collected for colpocytology and anal cytology. A polymerase chain reaction-based technique was used to detect HPV deoxyribonucleic acid in endocervical and anal swab samples. Results: the cervical and anal HPV positivity rates were 35.21% and 78.8%, respectively. The presence of HPV-related lesions on colpocytology was associated with anal HPV positivity (P = 0.027). The ratio between cervical HPV infection and cervical HPV-related lesions was 2.5. The ratio between anal HPV infection and anal HPV-related lesions was 4.3. Overall, 30% had concomitant HPV DNA in the cervix and anus. Conclusion: there are differences in the susceptibility of infections and related lesions between the cervix and anus. Despite a higher incidence of anal HPV, the progression to HPV-related lesion does not occur via the same manner in the cervix and anus. Moreover, cervical HPV-related lesions in HIV-positive women may serve as a cue for anal preventive strategies, and further investigations in these women may be useful.